Chicken biodiversity and their management under backyard production system in Southern Rajasthan - SP Tailor; S Mishra; BL Dangi; Anand Jain (Journal of Livestock Biodiversity, 2025)
The characterization of chicken biodiversity of southern Rajasthan was undertaken through stratified randomsampling survey of 300 poultry keepers from 60 villages in 12 tehsils of 6 districts. The information were collectedon flock size, physical characteristics, egg production traits, egg characteristics, management practices andconstraints in backyard poultry production system. All the surveyed farmers maintained coloured non-descriptbirds and followed backyard/free range system of rearing. The first choice was dual type in rural areas, closelyfollowed by egg type in nearby cities. The native birds had mixed plumage colour, dull colour pattern, yellow skinand shank colour, red ear lobe, red single comb, and black eye. Average age at first egg production was 6.78±0.05months and annual egg production was 43.16 ± 0.39 eggs. The average clutch size and pause period were 12.59 ±0.13 and 107.05 ± 0.52 days, respectively. The number hatch brooding per year by a hen was 2.88 ± 0.08, whileaverage chick hatched out per hatch was 9.52 ± 0.09. The average egg weight, length and breadth were 40.50±0.34 g,4.75+0.02 cm and 3.47+0.01 cm, respectively. The average body weight in adult male and females were 1.91±0.02and 1.25±0.04 kg. The average shank length in adult males and females were 8.35± 0.03 and 6.73±0.02 cm,respectively. The chickens were housed in katcha houses without proper bedding material. Predators posed majorconstraint for backyard poultry production in the region.